Antidiabetic Effect of Fraxetin Protective Role on the Levels of Glycoprotein Components in Experimental Diabetic Rats - N Ashokkumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Antidiabetic Effect of Fraxetin Protective Role on the Levels of Glycoprotein Components in Experimental Diabetic Rats